Is the Price Level Tied to the M2 Monetary Aggregate in the Long Run - Hallman, Jeffrey J.; Porter, Richard D.; Small, David H. (American Economic Review, 2007)
A long-run link between money and prices is evident for the United States since the Korean War if the M2 measure of money is used and the velocity of M2 (V2) is modeled as a mean-reverting series. This link between M2 and prices is the basis for a dynamic model of inflation that compares favorably in forecasting exercises with Phillips-curve and more typical monetarist approaches. The behavior of V2 is examined from 1870 to the present, providing a basis for reconsidering previous findings that V2 follows a random walk. Copyright 1991 by American Economic Association.